Autophagy modulation as a target for anticancer drug discovery - Li Xin; Xu Huai-long; Liu Yong-xi; An Na; Zhao Si; Bao Jin-ku (Acta Pharmacologica Sinica, 2016)
Xin LI#, Huai-long XU#, Yong-xi LIU, Na AN, Si ZHAO, Jin-ku BAO* School of Life Sciences & State Laboratory of Bio-resources and Eco-environment, Ministry of Education, Sichuan University, Chengdu 610064, China Autophagy, an evolutionarily conserved catabolic process involving the engulfment and degradation of non-essential or abnormal cellular organelles and proteins, is crucial for homeostatic maintenance in living cells. This highly regulated, multi-step process has been implicated in diverse diseases including cancer. Autophagy can function as either a promoter or a suppressor of cancer, which makes it a promising and challenging therapeutic target. Herein, we overview the regulatory mechanisms and dual roles of autophagy in cancer. We also describe some of the representative agents that exert their anticancer effects by regulating autophagy. Additionally, some emerging strategies aimed at modulating autophagy are discussed as having the potential for future anticancer drug discovery. In summary, these findings will provide valuable information to better utilize autophagy in the future development of anticancer therapeutics that meet clinical requirements. Keywords: autophagy; cancer; apoptosis; anti-cancer drug; microRNA We are grateful to Lei WU, Zi-jie WANG, and Rong SUN for their critical review of this manuscript. This work was supported by the National Natural Science Foundation of China (No 30970643, No 81173093 and No J1103518) and Special Program for Youth Science and Technology Innovative Research Group of Sichuan Province, China (No 2011JTD0026). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail baojinku@scu.edu.cn Received 2012-12-11 Accepted 2013-02-26